The Impact of Village Expansion on the Socioeconomic Life of the Community in Rempek Darussalam Village - Fachri, Zhul; Rispawati, Rispawati; Basariah, Basariah; Sumardi, Lalu (Universitas Islam Negeri Sumatera Utara, 2025)
Village expansion is an administrative policy that aims to accelerate public services and equitable development, this research is directed at five aspects, namely income distribution, type of work, level of education, housing conditions, and wealth ownership, the method used in this research is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The data analysis technique uses qualitative data analysis techniques with the steps of data collection, data reduction, data presentation, and conclusion drawing. The results showed that in terms of income distribution, although there was a general increase in income, in addition, village expansion had a positive impact on the variety of types of work in the community, with the emergence of new job opportunities in the Government and trade sectors, on the other hand, the level of community education tended to increase along with the increase in education facilities, and housing conditions experienced improvements, marked by an increase in the quality of buildings and access to basic facilities. In addition, community wealth ownership has increased, both in the form of productive and consumptive assets. Overall, village expansion contributed significantly to the improvement of the community's standard of living.